Biases in grant proposal success rates, funding rates and award sizes affect the geographical distribution of funding for biomedical research - Wahls, Wayne P. (PeerJ, 2016)
The ability of the United States to most efficiently make breakthroughs on the biology, diagnosis and treatment of human diseases requires that physicians and scientists in each state have equal access to federal research grants and grant dollars. However, despite legislative and administrative efforts to ensure equal access, the majority of funding for biomedical research is concentrated in a minority of states. To gain insight into the causes of such disparity, funding metrics were examined for all NIH research project grants (RPGs) from 2004 to 2013. State-by-state differences in per application success rates, per investigator funding rates, and average award size each contributed significantly to vast disparities (greater than 100-fold range) in per capita RPG funding to individual states. To the extent tested, there was no significant association overall between scientific productivity and per capita funding, suggesting that the unbalanced allocation of funding is unrelated to the quality of scientists in each state. These findings reveal key sources of bias in, and new insight into the accuracy of, the funding process. They also support evidence-based recommendations for how the NIH could better utilize the scientific talent and capacity that is present throughout the United States.
Keywords: Biomedical research; Federal funding; Science policy